DESA-DESA KUNA PANTAI SELATAN JAWA - Goenadi Nitihaminoto (BRIN, 2004)
Ancient villages referred to in this paper are villages located on the southern coast of Java which originated from the beginning of 1st to the 17th century AD. Ancient villages on the south coast of Java have been researched, so that the remnants of their life can be used as an indication of the existence of a community or a society that had activities in the coastal area. Communities that have activities in a village cannot be separated from communities in other villages and even have a direct or indirect relationship with the urban community that is closest to the village. Based on this position, when compared to other villages or cities in the north, the ancient villages on the coast are included in the outskirt villages or marginal villages. Based on this position, the villages had a high level of homogeneity in their ways of life, such as their livelihoods and beliefs, especially in the oldest villages.